Organophotocatalyst Enabled Deoxycyclopropanation of Alcohols - Yongsheng Zhang; Jincheng Wang; Xiaoyan He; Shilin Peng; Lei Yuan; Gang Huang; Yongjin Guo; Xiuhong Lu (Advanced Science)
Abstract Cyclopropane fragments, which widely exist in marketed drugs and natural products, can confer special pharmacological properties to small‐molecule drugs. Therefore, developing methods to construct cyclopropanes is of great significance. Nevertheless, the introduction of cyclopropane primarily relies on already‐formed cyclopropyl groups, which significantly restricts the diversity of cyclopropane skeletons. Late‐stage direct cyclopropanation is still a challenging task. Herein, a photo‐induced intermolecular deoxycyclopropanation reaction that employs alcohols as substrates, and 1 mol.% of 2,3,5,6‐tetrakis(carbazol‐9‐yl)‐1,4‐dicyanobenzene (4CzTPN) as organophotocatalyst is reported. This method proceeds with high transformation efficiency (up to 98% yield) and exhibits broad functional group tolerance, such as primary, secondary, and tertiary alcohols as well as various activated β‐halogenated alkenes. This process is mild, easy to operate, and has low equipment requirements. The power of this technology is demonstrated by the late‐stage functionalization of five marketed drugs and five natural products.